Filter Air Untuk Peningkatan Kualitas Air Pada Usaha Ikan Hias Kelurahan Tualang Kecamatan Perbaungan Serdang Bedagai - Siahaan, Kristianus Boby A.M.; Simanjuntak, Benrad E; Benar; Qadry, Al (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2024)
Betta fish is a type of ornamental fish that is very popular during the pandemic, so its selling price has experienced a spike. The reason why this fish is so popular is because of its tiny appearance with unique shape, as well as its extraordinary durability. Betta fish can survive in an aquarium for a long time even if they are not equipped with an aerator or air circulator. Maintenance is relatively easy, cultivation does not require a large space or large capital and can also be done as a home business. Mr. Suwandi, as the prospective service partner, has been running the ornamental fish cultivation business for this type of Betta fish for 5 years, where the fish are kept in tarpaulin fish ponds. There are around 29 fish ponds owned by partners with the number of fish per pond being around 200 to 300. The pool water source is dug well/ring well water where the pool water is replaced every 1.5 months. The quality of pond water greatly influences the sex of the fish produced. Male Betta fish can be sold for IDR 2,000 apiece, while females are only priced at IDR. 300 to 500. Because water quality has a big influence on the selling price, the implementation team added water filter installations after the well and before it flows into the pond. The water quality obtained after carrying out this activity was much better than the water samples obtained previously.